Maternal-filial transfer structures in endosperm: A nexus of nutritional dynamics and seed development. (February 2022) - Povilus, Rebecca A.; Gehring, Mary
Abstract: Although the ultimate purpose of a seed is the successful establishment of the next generation, seed development involves more than embryo growth. In angiosperms, seed development requires the intimate coordination of three distinct entities — maternal tissue and two offspring, embryo and embryo-nourishing endosperm. Although seeds are cornerstones of many terrestrial ecosystems and human diets, we are only beginning to understand the interactions among seed tissues and the molecular processes and genes that determine them. Recent studies of gene expression and function in distantly related angiosperms, combined with over 100 years of embryological research, have repeatedly highlighted the endosperm associated with maternal-filial boundaries as a central point in seed developmental dynamics. In this review, we highlight evidence that links this zone with nutritional dynamics, developmental signaling, and imprinted gene expression. We suggest that the underappreciated diversity of this specialized endosperm across angiosperms deserves further study from developmental, molecular, and genetic perspectives. Highlights: The endosperm, a biparental, nutritive seed tissue, differentiates into specialized zones. Transfer-specialized endosperm is found at maternal-filial boundaries in many species. Transfer endosperm functions in nutrient dynamics, developmental signaling, and gene imprinting. Distinct and diverse endosperm transfer structures (including haustoria) are found across angiosperms.